2018
DOI: 10.2147/ndt.s173659
|View full text |Cite
|
Sign up to set email alerts
|

PTSD patients show increasing cytokine levels during treatment despite reduced psychological distress

Abstract: BackgroundA reciprocal relationship between activated innate immune system and changes in mood and behavior has been established. There is still a paucity of knowledge on how the immune system responds during psychiatric treatment. We aimed to explore circulating cytokines and assess psychiatric symptom severity scores during 12 weeks of inpatient psychiatric treatment.MethodsThe study was a longitudinal assessment of 124 patients (88 women and 36 men) in treatment at Modum Psychiatric Center, Norway. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
(42 reference statements)
1
30
0
1
Order By: Relevance
“…Implicated in AD 39 and SCZ 60 Down 0.0217 0.6503 Down 0.2043 0.5761 Down 0.2474 0.599 Interleukin-1 receptor antagonist protein (IL-1ra) A cytokine involved in immune and inflammatory responses. Upregulated in SCZ 61 , PTSD 62 , and AD 63 Up 0.0241 0.6511 Up 0.2099 0.5932 Up 0.4326 0.5743 Fibroblast growth factor receptor 2 (FGFR2) Involved in neurogenesis and neurodegeneration, associated with BPD 64 and SCZ 65 Up 0.0259 0.6126 Up 0.2396 0.5616 Down 0.8937 0.5176 Ephrin type-A receptor 10 (EPHA10) Involved in mobility in neuronal and epithelial cells and memory formation, Eph/ephrin system is implicated in AD 39 Down 0.0265 0.5881 Down 0.5581 0.5334 Down 0.0167 0.7156 Gastrotropin (GT) Involved in fatty acid uptake, transport, and metabolism Down 0.0319 0.6046 Down 0.1769 0.5986 Down 0.2847 0.5871 Tumor necrosis factor receptor superfamily member 27 (EDA2R) Mediates cell–cell signaling, associated with age and developmental brain disorders including autism 66 Up 0.0346 0.7015 Up 0.6121 0.5973 Up 0.2194 0.6374 Ephrin-A4 (EFNA4) Implicated in mediating developmental events in the nervous system and autism …”
Section: Resultsmentioning
confidence: 99%
“…Implicated in AD 39 and SCZ 60 Down 0.0217 0.6503 Down 0.2043 0.5761 Down 0.2474 0.599 Interleukin-1 receptor antagonist protein (IL-1ra) A cytokine involved in immune and inflammatory responses. Upregulated in SCZ 61 , PTSD 62 , and AD 63 Up 0.0241 0.6511 Up 0.2099 0.5932 Up 0.4326 0.5743 Fibroblast growth factor receptor 2 (FGFR2) Involved in neurogenesis and neurodegeneration, associated with BPD 64 and SCZ 65 Up 0.0259 0.6126 Up 0.2396 0.5616 Down 0.8937 0.5176 Ephrin type-A receptor 10 (EPHA10) Involved in mobility in neuronal and epithelial cells and memory formation, Eph/ephrin system is implicated in AD 39 Down 0.0265 0.5881 Down 0.5581 0.5334 Down 0.0167 0.7156 Gastrotropin (GT) Involved in fatty acid uptake, transport, and metabolism Down 0.0319 0.6046 Down 0.1769 0.5986 Down 0.2847 0.5871 Tumor necrosis factor receptor superfamily member 27 (EDA2R) Mediates cell–cell signaling, associated with age and developmental brain disorders including autism 66 Up 0.0346 0.7015 Up 0.6121 0.5973 Up 0.2194 0.6374 Ephrin-A4 (EFNA4) Implicated in mediating developmental events in the nervous system and autism …”
Section: Resultsmentioning
confidence: 99%
“…release ( Figure 1) [3], thus triggering inflammation [4]. Accordingly, antidepressants were shown to reduce enhanced levels of cytokines [5].…”
Section: Psychological Stress and Agingmentioning
confidence: 98%
“…This suggests the involvement of neural, physiologic, molecular, and genomic mechanisms. Chronic psychological stress is also believed to stimulate pro-inflammatory cytokines release ( Figure 1) [3], thus triggering inflammation [4]. Accordingly, antidepressants were shown to reduce enhanced levels of cytokines [5].…”
Section: Psychological Stress and Agingmentioning
confidence: 99%
“…With a standardised mean difference of d = −0.54 (Köhler et al, 2014), the power was found to be 0.71, giving a 29% chance of not finding an effect even if present. Further, we specifically assessed the relationship between PTSD and GSI since we have previously found the PTSD patients to differ from patients without PTSD (Toft et al, 2018). We also assessed the relationship between anti-depressants and GSI in the aforementioned strata in order to distinguish potential effects of different drugs.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Meta-analyses and systematic reviews of cross-sectional studies have shown that circulating pro-inflammatory cytokines, such as interleukin (IL)-1, IL-6, and tumour necrosis factor-alpha (TNF-α), are significantly elevated in depressed individuals as well as in a broad spectre of other psychiatric diagnoses compared to healthy controls (Dowlati et al, 2010;Passos et al, 2015;Dalton et al, 2018). We have previously found both higher levels and a distinct escalation during treatment of pro-inflammatory and anti-inflammatory cytokines in patients with posttraumatic stress disorder (PTSD), but not for other psychiatric disorders (Toft et al, 2018). There is evidence of a causal pathway from low-grade inflammation to depression, as raised inflammatory markers have been found to precede depressive symptoms in longitudinal studies (Valkanova et al, 2013).…”
Section: Introductionmentioning
confidence: 99%